Mapping legal literacy in a rural community: a descriptive study of Darungan Village, Indonesia - Nursalim Nursalim; Wikan Sasmita; Etty Andyastuti; Agus Widodo; Suratman Suratman; Yunita Dwi Pristiani; Irawan Hadi Wiranata; Hamida Ulfa Fauziah; Mohammad Khoirul Muanam; Nasrudin Nasrudin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to map the level and configuration of legal literacy among residents of Darungan Village, Pare District, Kediri Regency, by examining four core dimensions: legal knowledge, legal awareness, attitudes toward the law, and legal behavior. The research adopts a descriptive quantitative approach. Data were collected from 100 adult village residents selected through purposive sampling using a structured questionnaire measured on a five-point Likert scale. Descriptive statistical analysis was employed to identify mean scores and categorical levels across each legal literacy dimension. The findings indicate that overall legal literacy in Darungan Village is categorized as high. Residents demonstrate strong legal awareness and positive attitudes toward the law, while legal knowledge and legal behavior show moderate variation across dimensions. Although normative compliance with legal rules is well established, active engagement in formal legal processes such as reporting violations and participating in legal education activities remains limited. These results suggest that high legal awareness and positive attitudes do not automatically translate into proactive legal behavior. The study implies that efforts to strengthen legal literacy in rural communities should move beyond information dissemination and address structural, cultural, and access-related factors that influence legal behavior. Mapping legal literacy empirically at the village level provides an important foundation for designing context-sensitive legal education and community empowerment strategies that are aligned with local social realities.